Lubuska przyroda - warta zachodu? = Nature of ziemia lubuska: is it worth protecting? - Gabryś, Grzegorz; Jerzak, Leszek; Gabryś, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ziemia Lubuska (Lubusz Land) is characterized by rich diversity of nature, which is protected within nine forms of nature conservation. There are two National Parks, 65 nature reserves, eight Landscape Parks, 74 Natura 2000 sites, 36 protected landscape areas, six Nature and landscape complexes, 335 ecological sites, and 1785 natural monuments.
Keywords: lubuskie; ochrona przyrody; zagrożenia; monitoring; Lubuskie Province; nature protection; endangerment